Genomic rearrangements in prostate cancer. Issue 1 (January 2015) - Barbieri, Christopher E.; Rubin, Mark A.
<x xml:space="preserve">Abstract</x> Purpose of review Genomic instability is a fundamental feature of human cancer, leading to the activation of oncogenes and inactivation of tumor suppressors. In prostate cancer (PCA), structural genomic rearrangements, resulting in gene fusions, amplifications, and deletions, are a critical mechanism effecting these alterations. Here, we review recent literature regarding the importance of genomic rearrangements in the pathogenesis of PCA and the potential impact on patient care. Recent findings Next-generation sequencing has revealed a striking abundance, complexity, and heterogeneity of genomic rearrangements in PCA. These recent studies have nominated a number of processes in predisposing PCA to genomic rearrangements, including androgen-induced transcription. Summary Structural rearrangements are the critical mechanism resulting in the characteristic genomic changes associated with PCA pathogenesis and progression. Future studies will determine whether the impact of these events on tumor phenotypes can be translated to clinical utility for patient prognosis and choices of management strategies.